Pengembangan Media Tepuk Gambar dalam Pembelajaran Bahasa Arab Maharah Al-Kalam di Madrasah Aliyah Negeri 1 Mojokerto - Katalaini, Muhammad Awaluddin; Indrawati, Ninik; Koniyo, Siti Nurhaliza (TARBAWIYAT, 2024)
This research is based on several problems and obstacles in the Arabic learning process, in particular; the aspects of ma>harah al-kalam. This happened due to lacking of the teacher's creativity and innovation in designing both an attractive and effective learning process. So that it results to the learning process where students seem to be monotonous and boring. The impact is that many students are being passive and the students do not exceed the maximal phase in interaction using Arabic. This research was designed using the Research and Development (R&D) method with the Bolg and Gall model which has been modified into 4 steps, namely; research and data collection, product planning, product development, and product validation. The research results were obtained from documentation, observation and validation results from media experts and material experts in the form of questionnaires. Material experts provide an assessment of three aspects, namely; relevance, accuracy, and suitability of the presentation with the demands of student-centred learning. With a percentage score of 87% with the category "very feasible". Based on these two results of data analysis from media experts and experts in learning media materials, it was obtained that the accumulated score was 78% in the "feasible" category. So, with these results the Tap Image learning media is suitable for learning Arabic in the aspects of maharah al-kalam.